Capital buffers in Middle East and North Africa (MENA) banks: is market discipline important?. Issue 2 (19th June 2017) - Ghosh, Saibal
Abstract : Purpose: The role of market discipline in influencing capital buffers has been debated in literature. Limited evidence on this score is available for Middle East and North Africa (MENA) countries. In this context, using data for 2001-2012, the paper aims to examine the role and relevance of market discipline in affecting capital buffer for MENA banks. Design/methodology/approach: Given the longitudinal nature of the data, the paper employs dynamic panel data techniques that take on board the potential endogeneity between the dependent and independent variables. Findings: The analysis indicates that the disciplining effect of depositors in MENA banks on capital buffer occurs primarily through the quantity channel, although this behaviour differs for banks with high versus those with low buffers. In particular, bigger banks which typically have thin capital cushion are much less subject to market discipline, presumably owing to their too-big-to-fail status. Originality/value: The analysis differs from the extant literature in three distinct ways. First, the paper examines the differential response of Islamic banks on capital buffers via market discipline. Second, several of these countries are primarily commodity exporters. Accordingly, the paper examines the behaviour of these countries with regard to market discipline. Third, how far did the global financial crisis impact bank capital buffer had not been explored in prior empirical research, an aspect that is addressed in this study.